Sedimentation and geomorphology of the Ruoergai Basin outlet reach at the source of the Yellow River: Response to the late quaternary glacial debris flow damming events - Shi, Lingfan; Wang, Ping; Hu, Gang; Ge, Yukui; Qin, Jintang; Yang, Huili; Wang, Huiying; Xu, Bo; Xiao, Ruiqing (Frontiers in Earth Science, 2023)
The Yellow River is China’s mother river and its evolution has great impact on the landform change of China. Fluvial terraces in the source of the Yellow River suggest that Ruoergai Basin was connected with the lower reach after ~10 ka, much younger than the uplift chronology of the Tibetan Plateau. In this study, the geomorphology and sedimentation of the Cairima–Ningmute River at the exit of the Ruoergai Basin were investigated. Combined with the optically stimulated luminescence dating of the sediments, the reconstructed fluvial geomorphology processes are as follows: during ~50–20 ka, coarse debris such as moraines and glacial mudflows from the Anyemaqen Shan and Xiqing Shan were unloaded to the Maqu valley in the bottleneck reach of the Ruoergai Basin outflow, causing river blockage and lake formation in the upper Ruoergai Basin; during ~20–12 ka, the headward erosion of the river accelerated from the downstream to the upstream and the barrier dam eroded, forming terraces; since ~12 ka, the Yellow River has cut through the Ruoergai Basin and has developed two levels of terraces based on lacustrine sediments. Our results suggest that glacial debris flow from the Anyemaqen Shan extensively accumulated at the basin-canyon bottleneck during the last glacial period, and when the amount of sediment accumulation exceeded the amount of river erosion, damming events occurred. The glacial-interglacial cycles during the Quaternary might generate repeated damming and cut-through of the Ruoergai Basin. The Ruoergai Basin should be connected with the lower reach before ~50 ka.